The labor supply and school attendance of black women in extended and nonextended households. - Macpherson, David A.; Jb, Stewart (American Economic Review, 1989)
This analysis compares the labor supply of black women in extended and nonextended households in the United States. two foci of the study are 1) the relationship between the labor supply of grandmothers and single mothers in extended households and 2) the interaction of labor force participation human capital accumulation and child care decisions. The study estimates a labor supply model using 1980 census data that endogenizes the decision to attend school. (EXCERPT)